2015
DOI: 10.1021/acs.langmuir.5b02448
|View full text |Cite
|
Sign up to set email alerts
|

On the Motion of Carbon Nanotube Clusters near Optical Fiber Tips: Thermophoresis, Radiative Pressure, and Convection Effects

Abstract: We analyze the motion of multiwalled carbon nanotubes clusters in water or ethanol upon irradiation with a 975 and 1550 nm laser beam guided by an optical fiber. Upon measuring the velocities of the nanotube clusters in and out of the laser beam cone, we were able to identify thermophoresis, convection and radiation pressure as the main driving forces that determine the equilibrium position of the dispersion at low optical powers: while thermophoresis and convection pull the clusters toward the laser beam axis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Experimentally, both mechanisms can be present and thus contribute to the short and long-time release process of fluids contained in the proposed device. Furthermore, bubbles may be generated as well during the heating process due to micro-thermal cavitation thus enhancing the marker solution release process [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Experimentally, both mechanisms can be present and thus contribute to the short and long-time release process of fluids contained in the proposed device. Furthermore, bubbles may be generated as well during the heating process due to micro-thermal cavitation thus enhancing the marker solution release process [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The discovery and understanding of thermophoresis have provided ample opportunities for applications including thermal precipitation, , particle separation, , drug delivery, energy conversion, , biomolecule manipulation, and interaction detection, and so forth. Thermophoresis was first discovered in liquids in 1856 by Ludwig, who observed salt diffusing in water against a temperature gradient.…”
Section: Simulation Models and Methodsmentioning
confidence: 99%
“…Thermophoresis in aerosols was first reported in 1870 by Tyndall, who found that dust particles can be pushed away from a heated surface in a dust-filled room. However, in spite of the wide applications , , of thermophoresis in fluids, it was not until more than a century later that thermophoresis at solid–solid interfaces was first predicted. In 2006, Schoen et al , demonstrated via molecular dynamics (MD) simulations that an axial temperature gradient along a single-walled carbon nanotube (SWCNT) would drive a confined nanoparticle to move toward the direction of decreasing temperature.…”
Section: Simulation Models and Methodsmentioning
confidence: 99%
See 2 more Smart Citations